FFT-based approach to longitudinal interpolation in single- and multi-slice helical CT - Xiaochuan Pan; La Riviere, P.J. (1999 IEEE Nuclear Science Symposium. Conference Record. 1999 Nuclear Science Symposium and Medical Imaging Conference (Cat. No.99CH37019), 1999)
Presents an approach to single- and multi-slice helical computed tomography (CT) image reconstruction that exploits the fast Fourier transform (FFT) and the Fourier shift theorem to generate from the helical projection data a set of fan-beam sinograms corresponding to equispaced transverse slices. Slice-by-slice reconstruction is then performed by use of two-dimensional (2D) fan-beam algorithms. A natural extension of the approach allows the redundancy of fan-beam data acquired over 360/spl deg/ to be exploited to decrease the effective longitudinal sampling interval. The approach is found to perform best at pitch 1 for the single-slice case and pitch 3 for the multi-slice case, when its sampling conditions are well satisfied, yielding high-quality transverse images and longitudinal aliasing and resolution properties superior to those of standard approaches based on linear interpolation.